Comparison of ground reaction force among stride types in baseball pitching - Chen, S.-W.; Tang, W.-T.; Kung, J.-T.; Hung, T.-Y.; Lin, W.-H.; Chen, Y.-L.; Burgee, D. J. (Sports Biomechanics, 2024)
This study aims to investigate the different ground reaction force (GRF) characteristics from different stride types. This study included 30 Taiwanese elite college and professional baseball pitchers. Each pitcher was classified into one of the following stride types: tall and fall (TF), dip and drive (DD), or mixed (MX). Our findings indicated that DD pitchers pressed their bodies forward earlier than TF pitchers. In contrast, the GRF of the pivot leg of TF pitchers increased slowly in the first half of the stride phase and continued to increase even after the stride leg touched the ground. This type of continuous pressing in TF was different from that in DD and MX pitchers, which decreased rapidly into the arm-cocking & acceleration phases. We conclude that the lower extremities were used differently by TF, DD and MX pitchers. This information could serve as a training guideline for coaches and pitchers to enhance training effectiveness, while simultaneously lowering injury risks.